EMPOWERMENT OF FAMILIES WITH PREGNANT WOMEN IN STUNTING PREVENTION IN TALANG JERINJING VILLAGE, RENGAT BARAT DISTRICT INDRAGIRI HULU DISTRICT - WITA, DESWITA DES; Kusumarini, Novita; Julita, Sety (Poltekkes Kemenkes Riau, 2023)
Stunting is a chronic malnutrition problem caused by a lack of nutritional intake for quite a long time, resulting in impaired growth in children, namely the child's height is lower or shorter (dwarf) than the standard age. Stunting prevention should be carried out from the time of pregnancy, so that the growth of the fetus in the womb can develop properly. The condition of a short child's body is often said to be a hereditary (genetic) factor from both parents, so that many people just accept it without doing anything to prevent it. In fact, as we know, genetics is a determinant of health that has the least influence when compared to behavioral, environmental (social, economic, cultural, political) and health care factors. In other words, stunting is a problem that can actually be prevented. The purpose of implementing this community service is to increase the independence of families with pregnant women in preventing stunting. This community service is carried out in Talang Jerinjing Village, the working area of the Pekan Heran Health Center from January to September 2022. The target of this community service is families with pregnant women in Talang Jerinjing Village The result of the activity: increasing the independence of families with pregnant women in efforts to prevent stunting from an early age. Keywords: Empowerment, family, pregnant women, prevention, stunting